1971
DOI: 10.1044/jshr.1402.271
|View full text |Cite
|
Sign up to set email alerts
|

Articulation and Stress/Juncture Production Under Oral Anesthetization and Masking

Abstract: Eight subjects, half of them naive and the other half aware of the purpose of the experiment, spoke 30 pairs of sentences involving the production of intricate stress/juncture patterns along with a passage containing all major consonant phonemes in English in various intraword positions. All subjects spoke all materials under: (1) normal conditions, (2) 110 dB re: 0.0002 ubar white noise masking, (3) extensive local anesthesia of the oral cavity, and (4) masking and anesthesia combined. Stress and juncture pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

1975
1975
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 0 publications
2
20
1
Order By: Relevance
“…For example, the loss of auditory feedback that occurs in post-lingually deaf individuals results in a gradual deterioration of speech production (see, for example, Cowie and Douglas-Cowie, 1983). By contrast, experimental evidence from studies in which physical perturbation was applied to the articulators showed that speakers have a great ability to compensate for perturbations, in spite of the lack of auditory feedback (Folkins and Abbs, 1975;Gammon et al, 1971;Kelso and Tuller, 1983;Borden, 1979). Although the latter findings could be interpreted as evidence that auditory feedback plays no role for the on-line control of speech production, Jones and Munhall (2003) pointed out that the presence of prostheses or bite blocks results in diminished somatosensory feedback.…”
Section: Introductionmentioning
confidence: 89%
“…For example, the loss of auditory feedback that occurs in post-lingually deaf individuals results in a gradual deterioration of speech production (see, for example, Cowie and Douglas-Cowie, 1983). By contrast, experimental evidence from studies in which physical perturbation was applied to the articulators showed that speakers have a great ability to compensate for perturbations, in spite of the lack of auditory feedback (Folkins and Abbs, 1975;Gammon et al, 1971;Kelso and Tuller, 1983;Borden, 1979). Although the latter findings could be interpreted as evidence that auditory feedback plays no role for the on-line control of speech production, Jones and Munhall (2003) pointed out that the presence of prostheses or bite blocks results in diminished somatosensory feedback.…”
Section: Introductionmentioning
confidence: 89%
“…Briefly, auditory feedback serves to validate articulatory/acoustic relations that underlie synergisms for phoneme production. ͑In-vestigators of deafened adult speech who have advanced some form of validation hypothesis include Gammon et al, 1971;Sherrard, 1982;and Waldstein, 1990.͒ In order to maintain intelligibility, auditory feedback also serves to monitor transmission conditions, leading the speaker to respond adaptivity with changes in average SPL, F0, and syllable duration by implementing changes in underlying speech ''postures,'' such as the balance between expiratory and inspiratory forces associated with a subglottal pressure, average tension in and separation of the vocal folds, and speaking rate. We hypothesize that changes in the variability of SPL and F0 contours reflect that same role of selfhearing; exaggerated SPL and F0 inflections serve to enhance intelligibility under adverse transmission conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These results are essentially in agree ment with previous research investigating the effects of masking noise on speech control. Ringel (1962) and Gammon et al (1971) found that under high levels of masking noise, fundamental frequency usually was higher and frequency variability tended to be greater than under no-noise conditions.…”
Section: Conversational Taskmentioning
confidence: 99%
“…Studies concerning modes of sensory monitoring have focused upon the oral region (McCroskey, 1958;Ringel and Steer, 1963;Gammon et al, 1971;Scott and Ringel, 1971;Putnam and Ringel, 1972;Leanderson, 1972;Borden et al, 1973a, b) almost to the exclusion of the laryngeal system. In fact, investigations pertaining to the larynx have often been tangential to the major purpose of the research.…”
mentioning
confidence: 99%